2016
DOI: 10.1242/jeb.142604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of series elastic compliance on muscle force summation and the rate of force rise

Abstract: Compliant tendons permit mechanically unfavourable fascicle dynamics during fixed-end contractions. The purpose of this study was to reduce the effective compliance of tendon and investigate how small reductions in active shortening affect twitch kinetics and contractile performance in response to a second stimulus. The series elastic element (SEE) of the human triceps surae (N=15) was effectively stiffened by applying a 55 ms rotation to the ankle, through a range of 5 deg, at the onset of twitch and doublet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 67 publications
3
50
0
Order By: Relevance
“…We argue that the higher velocity of active shortening afforded by the compliant tendon was sufficient to cause a considerable reduction in the force-generating capacity of the contractile apparatus during force development, such that the relative force contribution of a second stimulating pulse was reduced with respect to stiffer conditions. Twitch force has been shown to increase significantly in response to a modest reduction in the velocity of shortening induced by an increase in SEE effective stiffness (Mayfield et al, 2016). Sandercock (2000) also concluded that a higher velocity of active shortening during force development could likely explain the reduction in force summation demonstrated when individual parts of whole muscle were activated simultaneously rather than individually, arguing that a common SEE permitted greater internal shortening during synchronous activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that the higher velocity of active shortening afforded by the compliant tendon was sufficient to cause a considerable reduction in the force-generating capacity of the contractile apparatus during force development, such that the relative force contribution of a second stimulating pulse was reduced with respect to stiffer conditions. Twitch force has been shown to increase significantly in response to a modest reduction in the velocity of shortening induced by an increase in SEE effective stiffness (Mayfield et al, 2016). Sandercock (2000) also concluded that a higher velocity of active shortening during force development could likely explain the reduction in force summation demonstrated when individual parts of whole muscle were activated simultaneously rather than individually, arguing that a common SEE permitted greater internal shortening during synchronous activity.…”
Section: Discussionmentioning
confidence: 99%
“…A similar response was observed when active shortening against the stretch of the SEE was largely prevented by a feedback control signal that adjusted the length of an isolated bullfrog plantaris MTU (Sawicki and Roberts, 2009). We recently demonstrated for the human triceps surae, which has high fixed-end compliance, that the mechanical properties of the twitch could be dramatically increased by only a modest reduction in fascicle shortening amplitude and velocity induced by a rapid stretch of relatively low amplitude (Mayfield et al, 2016). Stretch of the MTU early in the twitch was shown to also influence the force generated by a second stimulating pulse delivered at the post-stretch MTU length, suggesting that the depressant effect of active shortening on contractile force may influence force summation under conditions where internal shortening is permitted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Mayfield et al. ), of which only Sale and colleagues measured components of plantar flexor relaxation. Using electrical stimulation of the tibial nerve at rest, Sale and colleagues found half‐relaxation time to be slower at 20° DF (139.0 ± 26.5 ms) compared to 30° PF (89.5 ± 21.4 ms).…”
Section: Discussionmentioning
confidence: 99%
“…; Mayfield et al. ). Hence, no study has paired TMS with ultrasound to assess intrinsic contractile properties while the muscle is actively contracting.…”
Section: Introductionmentioning
confidence: 98%